Changes in Specific Biomarkers Indicate Cardiac Adaptive and Anti-inflammatory Response of Repeated Recreational SCUBA Diving - Dumić, Jerka; Cvetko, Ana; Abramović, Irena; Šupraha Goreta, Sandra; Perović, Antonija; Njire Bratičević, Marina; Kifer, Domagoj; Sinčić, Nino; Gornik, Olga; Žarak, Marko (Frontiers in Cardiovascular Medicine, 2022)
Objective: Recreational SCUBA (rSCUBA) diving has become a highly popular and widespread sport. Yet, information on molecular events underlying (patho)physiological events that follow exposure to the specific environmental conditions (hyperbaric conditions, coldness, immersion, and elevated breathing pressure), in which rSCUBA diving is performed, remain largely unknown. Our previous study suggested that repeated rSCUBA diving triggers an adaptive response of cardiovascular and immune system. To elucidate further molecular events underlying cardiac and immune system adaptation and to exclude possible adverse effects we measured blood levels of specific cardiac and inflammation markers. Methods: This longitudinal intervention study included fourteen recreational divers who performed five dives, one per week, on the depth 20-30 m that lasted 30 min, after the non-dive period of 5 months. Blood samples were taken immediately before and after the first, third, and fifth dives. Copeptin, immunoglobulins (IgA, IgG, and IgM), complement components C3 and C4, and differential blood count parameters, including neutrophil-to-lymphocyte ratio (NLR) were determined using standard laboratory methods. Cell-free DNA was measured by qPCR analysis and N-glycans released from IgG and total plasma proteins (TPP), were analyzed by hydrophilic interaction ultra-performance liquid chromatography. Results: Copeptin level increased after the first dive but decreased after the third and fifth dive. Increases in immunoglobulins level after every dive and during whole studied period were observed, but no changes in C3, C4, and cfDNA level were detected. NLR increased only after the first dive. IgG and TPP N-glycosylation alterations toward anti-inflammatory status over whole studied period were manifested as an increase in monogalyctosylated and core-fucosylated IgG N-glycans and decrease in agalactosylated TPP N-glycans. Conclusion: rSCUBA diving practiced on a regular basis promotes anti-inflammatory status thus contributing cardioprotection and conferring multiple health benefits.